Challenges and opportunities for early childhood intervention services in Singapore: addressing user satisfaction - Kim, Soojin; Zhang, Xinwei; Sawant, Sachi; Poon, Kenneth K.; Khoo, Poh Choo; Wong, Chui Mae; Daniel, Lourdes Mary; Law, Evelyn C.; Lee, Elene; Leong, Victoria (Frontiers in Public Health, 2025)
Since the COVID-19 pandemic, there has been a gap between primary stakeholders' ex ante expectations of adaptive early childhood intervention (ECI) services and their actual experiences with these services. This is despite governments' and service operators' swift pivot from on-site service delivery to home-based, virtual and hybrid modes, and cross-sector collaboration with private providers and pre-schools. In this article, we share our preliminary evidence from in-depth interviews with parents and clinicians regarding the perceived challenges to post-pandemic ECI services. We discuss how the crisis has triggered a paradigm change, especially regarding potential drivers for satisfactory services in the Singapore context.